ADAPTIVE LEARNING IN COLLEGEIN THE PANDEMIC TIME COVID-19 - wahyu wahyu (Universitas Lambung Mangkurat, 2021)
The Covid-19 virus has triggered chaos in various fields of life globally, including education. Holding activities to gain knowledge together is no longer recommended to be held. Many countries eliminate face-to-face learning and replace it with online learning line. This policy was implemented to reduce the spread of the Covid-19 Virus. In line with these efforts, campuses as a place to forge themselves with knowledge also need to have a strategy to help reduce the spread of Covid-19. Efforts to prevent the spread of Covid-19 in the campus environment will be in line with the government's appeal, namely to organize online learning at home. Online learning creates logical consequences, for the perpetrators, both for students and teachers. One side of online learning is an alternative to minimizing the possibility of crowding, but online learning also creates challenges to present material in a manner that can accommodate scientific demands. Despite the challenges, online learning is certainly expected to foster an attitude of optimism, provide challenges and opportunities to develop student innovation, creativity, capacity, personality and needs. The solution, lecturers are required to have abilities in the field of learning technology. Another logical consequence is that higher education leaders must be active in optimizing the performance of using online facilities for all lecturers, students, and educational staff.